2011
DOI: 10.1111/j.1834-7819.2011.01320.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of unstimulated saliva cortisol level with severity of oral dryness feeling in menopausal women

Abstract: Background: Menopause may be associated with some adverse changes, such as oral dryness (OD) feeling. The exact mechanisms that mediate sensation of OD in menopausal women have not been firmly established. The purpose of this study was to assess the relationship of unstimulated whole saliva cortisol level with severity of OD feeling in menopausal women. Methods: A case control study was carried out on 70 selected menopausal women with ⁄ without OD feeling, conducted at the Clinic of Oral Medicine, Tehran Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…This fact is supported by clinical trials showing a reduction in salivary flow during menopause [8,16,18]. In addition to the quantitative change, case-control studies have shown changes in the concentrations of substances in the saliva of women in menopause and xerostomia [5,[19][20][21][22]. However, the exclusive development of xerostomia in older people is still a matter of debate.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This fact is supported by clinical trials showing a reduction in salivary flow during menopause [8,16,18]. In addition to the quantitative change, case-control studies have shown changes in the concentrations of substances in the saliva of women in menopause and xerostomia [5,[19][20][21][22]. However, the exclusive development of xerostomia in older people is still a matter of debate.…”
Section: Discussionmentioning
confidence: 91%
“…Xerostomia is the subjective feeling of dryness in the mouth as a result of the reduction or interruption of the salivary gland function accompanied by changes in quantity or quality of saliva [4,5]. The diagnosis of xerostomia and/or reduced salivary flow is basically made in a clinical way and should take into account the various medications that can cause or exacerbate the condition [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several evidence has been proven and suggested using saliva tests to diagnose, monitor, and predict disease prognosis. It has been indicated that numerous biochemical molecules can be assayed in saliva of patients, for example, cortisol (15), progesterone (16), 17β-estradiol (17), CA15-3 (18), CA125 (19), creatine kinase MB (8), creatine phosphokinase (20), parathyroid hormone (21), cathepsin (22), hc-CRP (23), and aminotransaminase (24). Much attention has been paid to saliva as a biological sample because of the rapid, uncomplicated and non-invasive nature of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects used for this study were females in the postmenopause period, age of 45e55 years, cessation of menstruation for at least 12 continuous months and with or without a complain of xerostomia. Patient having any of the following are not involved in the current study: To diagnose xerostomia, a questionnaire was applied to the patients to be answered by yes or no illustrating presence of xerostomia [35,36] (Table 1).…”
Section: Methodsmentioning
confidence: 99%